The Effect of Moringa oleifera Leaf Extract on C2C12 Myoblast Proliferation and Redox Status Under Oxidative Insult - Roberta Ceci; Mariateresa Maldini; Piergiorgio La Rosa; Laura Sireno; Cristina Antinozzi; Mark E. Olson; Ivan Dimauro; Guglielmo Duranti (Antioxidants, 2024)
Skeletal muscle tissue can regenerate after damage through the action of satellite cells, which proliferate as myoblasts when activated. Oxidative stress, marked by high rates of reactive oxygen species (e.g., hydrogen peroxide, H2O2), impairs this process by increasing myoblast cell death. Moringa oleifera leaf extract (MOLE), known for its antioxidant properties, was tested for its protective effects on C2C12 myoblasts under oxidative stress. We assessed MOLE’s impact on total antioxidant capacity (TAC), glutathione homeostasis (GSH/GSSG), cell viability, and wound recovery. The metabolomic analysis of MOLE using an LC-MSMS ZenoTOF 7600 mass spectrometry system identified key compounds, including peculiar glucosinolates (42.1%) and flavonoids (18.8%), as well as phenolic acids (4.5%) and other significant metabolites (34.6%; among them, amino acids, vitamins, and fatty acids). H2O2 disrupted myoblast redox balance and caused cell death, but MOLE treatment restored the GSH/GSSG ratio, improved TAC, and increased cell viability. Additionally, MOLE promoted faster wound closure in myoblasts exposed to H2O2. These findings suggest that MOLE can protect C2C12 myoblasts by restoring redox balance and enhancing recovery under oxidative stress.